Pre-participation medical evaluation in competitive athletes: the experience of an international multisport club - Pi-Rusinol, R.; Sanz-de la Garza, M.; Grazioli, G.; García, M.; Sitges, M.; Drobnic, F. (Apunts Sports Medicine, 2022)
Objective to assess the effectiveness of a tailored Pre-Participation Medical Examination (PPME) prior to sport practice for athletes competing in team sports, has been suggested as a useful tool for an early identification and treatment of multiple disorders.